Pengaruh Jumlah Penduduk, Pendidikan, dan Pengangguran Pada Jumlah Penduduk Miskin Di Jawa Tengah - Husna, Arinal (UNPERBA, 2024)
This study aims to examine the effect of population, education, and unemployment on the number of poor people in Central Java in 2021. the sample applied is data on population, education, unemployment, and the number of poor people in all regencies/cities in Central Java Province in 2021. This research uses a quantitative approach. The research was taken from secondary data belonging to the Central Bureau of Statistics. The results of this study state that population has a positive and significant effect, the higher the population, the higher the number of poor people, and vice versa. Meanwhile, education has a significant negative effect. Unemployment has a negative and insignificant effect, the high and low unemployment does not affect the number of poor people. The results also show that population, education, and unemployment simultaneously affect the number of poor people in Central Java in 2021. The implications of this study suggest that policymakers should focus on improving educational access and quality to reduce poverty effectively. Furthermore, effective population control policies are necessary to manage the positive correlation between population growth and poverty. Future research should include additional variables such as health access, infrastructure, and comprehensive longitudinal data to provide a more detailed understanding of poverty dynamics.